2017
DOI: 10.1007/s00408-017-9996-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Cough Monitoring Using Ambient Sound Recording During Convalescence from a COPD Exacerbation

Abstract: PurposeCough is common in chronic obstructive pulmonary disease (COPD) and is associated with frequent exacerbations and increased mortality. Cough increases during acute exacerbations (AE-COPD), representing a possible metric of clinical deterioration. Conventional cough monitors accurately report cough counts over short time periods. We describe a novel monitoring system which we used to record cough continuously for up to 45 days during AE-COPD convalescence.MethodsThis is a longitudinal, observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 13 publications
0
18
1
2
Order By: Relevance
“…In recent years, it has been recognized that objective evaluations of cough are vital, and in some previous studies, cough frequency has been shown to be an important factor for monitoring the clinical state of patients with respiratory diseases, such as asthma and chronic obstructive pulmonary disease [13,[16][17][18]. In these kinds of studies, cough monitors with audio recordings are generally used.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been recognized that objective evaluations of cough are vital, and in some previous studies, cough frequency has been shown to be an important factor for monitoring the clinical state of patients with respiratory diseases, such as asthma and chronic obstructive pulmonary disease [13,[16][17][18]. In these kinds of studies, cough monitors with audio recordings are generally used.…”
Section: Discussionmentioning
confidence: 99%
“…With submaximal load no failure of the mesh-tissue-interface is observed with increasing pressures below a threshold of about 150 mmHg [ 4 , 11 ]. In patients, up to 400 coughs were observed within 24 h which can reach intraabdominal pressures well above 200 mmHg [ 12 , 13 ]. Using a self-built device delivering dynamic impact strain (DIS) simulating coughing actions, repeated impacts can rapidly impair ventral hernia repair [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the hospitalized patients in this study have these symptoms to varying degrees, and it is difficult to quantify the changes and severity of these symptoms in the medical records. Some studies use a sound monitoring system to continuously record a patient’s cough and perform an automated analysis to assess the severity of cough [28]. However, it is still difficult to guide clinical practice in the short term.…”
Section: Discussionmentioning
confidence: 99%